(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
A study of pattern of accidental deaths conducted at M.S. Ramaiah Medical College, Bangalore, between October 2007 and September 2009 in the age group of 1-18 years with aims and objectives to study percentage of accidental deaths in children, age and sex distribution, various patterns, manner of death and other factors associated with accidental deaths. Detailed information regarding the circumstances of death was sought from the police, relatives and friends, visits to the scene of occurrence or deduced by the photograph of the scene of occurrence. Accidental deaths in children constituted 3.24% (57 cases) of the total autopsies conducted. Maximum number of child deaths occurred in the age group of 15-18 years in males and 5-9 years in females. Male outnumbered the females. Majority of the children were preschool and school going and from middle and lower socioeconomic status. Road traffic accident accounted for 53% of the cases. Most of the children were pedestrians. Heavy motor vehicle was involved in majority of the cases and most of the children died due to head injury. Drowning accounts for 32% of the cases. Most of the children died due to accidental drowning while playing. Pond was the commonest place of drowning followed by sump. Thermal deaths accounts for 6.34% of the cases followed by fall from height, which accounts for the 6.34% of the cases, and only one case was due scorpion sting.